COMPLEXITIES IN TEACHING ENGLISH IN HIGHER SECONDARY LEVEL: A STUDY OF FOUR COLLEGES IN BOGURA DISTRICT, BANGLADESH - Md. Sabbir Hossain; Md. Nazmul Haque (Universitas Islam Sumatera Utara, 2022)
This paper aims to explore the challenges of English language teaching in the Bogura district, Bangladesh. Although Bogura is advanced in establishing educational institutions and trades, it is still lagging in respect of the quality and consequence of English language teaching in higher secondary education. In comparison to the other subject, it seems much more difficult for both teachers and learners. Therefore, the problems of English language learning have been listed, and the result of class observation of colleges in the Bogura district has been presented. To do this study, a descriptive research design, quantitative method, and questionnaires are used. The present findings opine that the majorities depend on the exam system to just pass the exam and there is no equal chance to be skilled in four skills of the English language students. The lacking of teachers has also been detected. However, the study attempts to illuminate a scenario of the English teaching system as well as the problems and prospects of English language learning and teaching in higher secondary education.